2021
DOI: 10.1038/s41598-021-87699-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and potential health risk of fluoride in drinking groundwater sources of Huaibei, Anhui Province

Abstract: Fluoride enrichment in drinking groundwater at Huaibei leads to potential health risk to the residents. A total of 49 groundwater samples from groundwater sources were collected to evaluate the potential health risk of fluoride ingestion through drinking water for children and adults in Huaibei. Results shown that the average concentration of fluoride in centralized sources is less than that of decentralized sources, which may be attributed to different geological conditions including fluoride-rich minerals, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 37 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…According to [59], the high fluoride content does not come from residual seawater, as may be the case for chloride and Sodium. They would come from the interaction between groundwater and rock from fluoride minerals associated with phosphate sediments (e.g., apatite fluoride) as also evidenced in other studies [63] [64] [65].…”
Section: Spatial Variation Of Groundwater Parametersmentioning
confidence: 58%
“…According to [59], the high fluoride content does not come from residual seawater, as may be the case for chloride and Sodium. They would come from the interaction between groundwater and rock from fluoride minerals associated with phosphate sediments (e.g., apatite fluoride) as also evidenced in other studies [63] [64] [65].…”
Section: Spatial Variation Of Groundwater Parametersmentioning
confidence: 58%
“…Consumable water in China contains a dangerous concentration of arsenic, fluorine, and sulfates (5), and an excess intake of fluoride and nitrate is associated with an increased risk of OA (6)(7)(8). In China, chemical and phosphate fertilizer plants discharge waste gas with fluorine into natural water sources (9,10). Except for Shanghai and Hainan, the fluorine level for drinking water in most parts of China is over the limit (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…In China, chemical and phosphate fertilizer plants discharge waste gas with fluorine into natural water sources (9,10). Except for Shanghai and Hainan, the fluorine level for drinking water in most parts of China is over the limit (9,10). An epidemiological study suggested a connection between OA prevalence and water districts contaminated with perfluorooctanoate (PFOA) and perfluorooctane sulfonate (PFOS) (6).…”
Section: Introductionmentioning
confidence: 99%
“…A daily intake of more than 2.4 mg for children aged 8-16 years and 3.5 mg for people aged >16 years may lead to fluorosis and adverse health effects (6). In Ethiopia, India, Tanzania, Mexico, China and other countries, the average fluoride concentration in drinking water is approximately 2 mg/L (7)(8)(9)(10)(11)(12). Therefore, the World Health Organization has set the maximum fluoride concentration in water to 1.5 mg/L (13).…”
mentioning
confidence: 99%